Cephalopods in the diet of keystone-species animals in the region of the Argentine Islands Archipelago (West Antarctica) - Dykyy, I.; Zahorodnyi, I. (Ukrainian Antarctic Journal, 2019)
Оbjective. The study of diet of keystone-species vertebrates (Nothotenia coriiceps, Phalacrocorax bransfieldensis, Leptonychotes weddellii) in the ecosystem of the Argentine Islands Archipelago. Methods. Biological researches were conducted on Akademik Vernadsky station during wintering in 2006—2007, 2009—2010, 2011—2012, 2019 accordance with tasks of the State Special-Purpose Research Program in Antarctica for 2011–2020. In total, the content of 30 faeces of the L. weddellii, 64 pellets and three stomachs of the Ph. bransfieldensis and 40 stomachs of the N. coriiceps were analyzed. Material was collected at all seasons. Results. The L. weddellii diet is dominated by three squid species Galiteuthis glacialis (39,5%), Brachiotheutis picta (21%) and the fishery species Psychroteuthis glacialis (15.8%). In the diet of Ph. bransfieldensis were found the main four Octopus species such as Adelieledone polimorpha – 20%, Pareledone turqueti – 20%, and Graneledone sp. – 24% and Benthoctopus sp. – 16%, who owns the highest proportion of hits. In the nutrition of N. coriiceps, cephalopods are rarely recorded. Only one species of Octopus has been registered and has been identified only to the Cirroteuthidae family. Conclusions. Found that in the diet of keystone-species vertebrates (N. coriiceps, Ph. bransfieldensis, L. weddellii) in the ecosystem of the Argentine Islands Archipelago there are 13 species of Cephalopods, of which 4 species belong to squid Decapoda and 9 species to octopuses Octopoda (3 species are identified to the genus and one to the family). The findings are important not only to establish the actual status of the Antarctic ecosystem and to conserve biodiversity in the Antarctic region.